Explaining the Argentine growth paradox: new evidence applying cointegration techniques - Federico Foders; Hans H. Glismann (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1992)
In this paper we revisit three hypotheses, which we had proposed before, in an attempt to explain the long-run pattern of Argentine real GDP growth: (i) distributional conflicts (between the government and the private sector, and between entrepreneurs and trade unions), (ii) a permissive monetary policy, and (iii) the delinking of the Argentine economy from the world markets. Applying unit root econometrics we determine that the model is not cointegrated and that it should be estimated with conventional methods in difference form. Alternative estimates . indicate that the best fit is achieved by a model representing hypotheses (i) and (ii) but not (iii). Thus, foreign trade seems not to have had any impact on Argentine GDP during the period studied. Also, the conflict between entrepreneurs and trade unions does not seem to have had an important influence on Argentine growth, at least in the period 1915 - 1978. However, the results for the extended period 1915 - 1988 indicate that our model representing hypotheses (i) and (ii) does not perform well in explaining the 1980s, when substantial changes in economic policy took place in Argentina.
Keywords: 330; Wirtschaftswachstum; Argentinien